THE IMPACT OF THE COVID-19 PANDEMIC ON MATERNAL MORTALITY ATTRIBUTES - Dyah Ayu Fatmaningrum; Wahyul Anis; Muhammad Ardian Cahya Laksana (Universitas Airlangga, 2022)
Background: The COVID-19 pandemic is a challenge for mothers to access health services in Indonesia. Patient management, referral processes, and maternal screening protocols are the reasons for this issue. Aims: This study aimed to analyze maternal mortality trends in East Java Province before and during the COVID-19 pandemic. Methods: This study was conducted using retrospective observation with a cross-sectional design, and samples were selected using a total sampling technique. The number of maternal deaths in East Java was 520 in 2019 and 565 in 2020. The independent variable in this study is the number of maternal deaths, and the dependent variables include age, gravida, place of death, rescue relay, time of death, and maternal complications. The variables of age, place of death, rescue relay, and gravida were assessed using the Chi-square test. Results: Statistical tests showed a ρ value of 0.195 for age; 0.916 for place of death; 0.646 for rescue relay; and 0.048 for gravida. Conclusion: Maternal mortality showed different trends before and after the pandemic in East Java. Significant differences in maternal mortality rate are influenced by gravida status.